Pemeliharaan Kesehatan Secara Holistik Melalui Perspektif Al-Qur’an dan Hadits Melalui Pemanfaatan Tanaman Herbal - Sahrul Muayyad. A; Syaila Sahra; Tasya Ruspita (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
This study also highlights the importance of applying Islamic health principles in daily life, such as maintaining a balanced lifestyle, managing stress through worship, and utilizing herbal plants as a form of treatment in accordance with religious teachings. The findings show that herbal plants not only provide biological benefits to the body's health, but also have profound psychological impacts, such as increasing gratitude to Allah Swt. and belief in the blessings of nature. By integrating Islamic teachings and scientific knowledge, this research offers a holistic approach that can be an effective solution to modern health challenges, while strengthening the spiritual aspects of Muslims. It is hoped that this article will make a practical contribution in promoting a healthy lifestyle based on. This research emphasizes the importance of combining health principles in Islam with modern science to achieve optimal well-being. The study examines how the adoption of an Islamic lifestyle, such as maintaining a healthy diet, worshiping regularly, and utilizing herbal plants, can have a positive impact on physical and mental health. The article concludes that by referring to the Quran and hadith, Muslims can develop a balanced healthy lifestyle. The findings are expected to make a real contribution in overcoming various health challenges in the modern era and encourage people to live more quality lives in accordance with religious teachings.